Architecture and interior design : an integrated history to the present - Harwood, Buie.; May, Bridget; Sherman, Curt. (Boston : Prentice Hall, 2012)
Combined and edited version of 2 separately published works: Architecture and interior design through the 18th century, and Architecture and interior design from the 19th century.
Precedents -- East Asia -- Antiquity -- Middle Ages -- Renaissance -- Baroque -- Rococo -- Early Neoclassic -- Revolution -- Late Neoclassic -- Victorian revivals -- Academic historicism -- Reforms -- Innovation -- Modernism -- Experimentation.
Combined and edited version of 2 separately published works: Architecture and interior design through the 18th century, and Architecture and interior design from the 19th century.
Includes bibliographical references (pages 839-849) and index.
Keywords: Interior decoration -- History; Interior architecture -- History; Decorative arts -- History